Valve-Preserving Repair of Very Late Type A Aortic Dissection Following Self-Expanding TAVI in an Octogenarian Patient: Case Report and Focused Narrative Review of the Literature - Lorenzo Giovannico; Giuseppe Fischetti; Domenico Parigino; Luca Savino; Claudia Leo; Giuseppe Cristiano; Giuseppe Scrascia; Massimiliano Carrozzini; Massimo Padalino; Tomaso Bottio (Journal of Cardiovascular Development and Disease, 2026)
Introduction: Acute type A aortic dissection (ATAAD) is a rare but potentially catastrophic complication following transcatheter aortic valve implantation (TAVI). Most reported cases occur during or shortly after the procedure and are attributed to procedural aortic injury. Very late presentations occurring years after successful TAVI are exceptionally uncommon, and evidence regarding their optimal management remains limited. Case Presentation: An 86-year-old man presented with acute chest pain four years after transfemoral implantation of a self-expanding Evolut R 29-mm transcatheter heart valve. Transthoracic echocardiography revealed pericardial effusion with signs of impending cardiac tamponade. Computed tomography angiography confirmed Stanford type A acute aortic dissection involving the ascending aorta. Emergency surgical repair was performed through replacement of the ascending aorta and hemiarch using a vascular graft. The previously implanted transcatheter valve was preserved because it remained structurally intact and functionally normal. The postoperative course was uneventful, and the patient was discharged on postoperative day 9 with preserved prosthetic valve function (mean gradient 11 mmHg, peak velocity of 2.1 m/s, EOA 1.8 cm2, EF 50%, TAPSE 18 mm and no evidence of paravalvular or intraprosthetic regurgitation). Discussion: To better contextualize this rare presentation, a focused review of the literature on delayed and late ATAAD after TAVI was performed. Only a limited number of cases were identified, highlighting the exceptional rarity of this complication. Reported management strategies included conservative treatment, endovascular interventions, and open surgical repair, with considerable heterogeneity in outcomes. Compared with previously published reports, the present case is notable for the exceptionally long interval between TAVI and dissection onset and for the successful valve-preserving surgical repair. These findings suggest that emergency surgery with preservation of a functioning transcatheter valve may be a feasible option in carefully selected patients. Conclusions: Very late ATAAD after TAVI is an exceptionally rare but life-threatening condition. This case demonstrates that valve-preserving surgical repair can be successfully performed even in selected octogenarian patients. As the population of long-term TAVI survivors continues to expand, awareness of late aortic complications, prompt diagnosis, and referral to specialized aortic centers remain essential for achieving favorable outcomes.